1999
DOI: 10.4148/1090-7025.1015
|View full text |Cite
|
Sign up to set email alerts
|

Phytoextraction of Metals from Contaminated Soil: A Review of Plant/Soil/Metal Interaction and Assessment of Pertinent Agronomic Issues

Abstract: Phytoremediation is an emerging technology that employs the use of higher plants for the cleanup of contaminated environments. Fundamental and applied research have unequivocally demonstrated that selected plant species possess the genetic potential to remove, degrade, metabolize, or immobilize a wide range of contaminants. Despite this tremendous potential, phytoremediation is yet to become a commercial technology. Progress in the field is precluded by limited knowledge of basic plant remedial mechanisms. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
201
0
25

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(243 citation statements)
references
References 57 publications
1
201
0
25
Order By: Relevance
“…Also, the immobilization of elements by root adsorption may be of some importance. This mechanism avoids element's translocation from roots to shoots in some species working as a defense barrier, decreasing the phytoextraction potential of such species since only a small part of ions associated to the roots are effectively absorbed (Lasat, 2000). Silva et al (2007) used soybean and rice to evaluate the absorption and capacity of translocation of heavy metals in the same soil studied here and observed that the roots limited the translocation of copper and lead to the aerial parts of both cultures.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, the immobilization of elements by root adsorption may be of some importance. This mechanism avoids element's translocation from roots to shoots in some species working as a defense barrier, decreasing the phytoextraction potential of such species since only a small part of ions associated to the roots are effectively absorbed (Lasat, 2000). Silva et al (2007) used soybean and rice to evaluate the absorption and capacity of translocation of heavy metals in the same soil studied here and observed that the roots limited the translocation of copper and lead to the aerial parts of both cultures.…”
Section: Resultsmentioning
confidence: 99%
“…These indicators allowed estimating also the period of time necessary to remove all soil contamination, considering four annual cultivation cycles. Soil decontamination is considered successful when the plants are able to extract up to 1 -2% of the metal from soil (Lasat, 2000) or up to 1% of Zn and Cu, 0.6% of Pb total content from soil (Garbisu and Alkorta, 2001).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike organic compounds, metals cannot be degraded (Lasat, 2000). To decrease the contents and bioavailability of heavy metals usually requires their removal.…”
Section: Introductionmentioning
confidence: 99%
“…The addition of chemical immobilization amendments may only immobilize lethal levels for restricted periods of time and introduce some other chemicals. Phytoremediation is recognized as the most commercially and environmental friendly available technology (Lasat, 2000), but up to now, only a limited number of plants have been found to have the phytoaccumulation ability and much less can be used for field phytoremediation because of low biomass production.…”
Section: Introductionmentioning
confidence: 99%